IMPROVING SPEAKING ABILITY BY USING PICTURE SERIES - Masula; Sholichah, Norma Ita (Center for the Research and the Community Service, Islamic Institut of Hasanuddin Pare - Kediri, 2024)
This research aims to find out whether there is an influence of the Tik Tok channel nofreeadi10 application on the speaking development of 8 MTS An-Nur Sumberurip. This research uses qualitative research methods in this research to make it easier, the researcher acts as documentation and reference by collecting data directly through interviews, observation and documentation. Interviews were conducted with grade 8 students and the English teacher at MTS An-Nur Sumberurip. From the results of the research conducted, the speaking skills of students in class 8 are very low due to: 1) lack of honing their speaking skills 2) school facilities. The researcher asked the English teacher for help in conducting speaking lessons via the TikTok channel nofreaadi10 to find out the effect of this method on students' speaking abilities. English language teachers use this method in between lessons.